Model of an Open Microeconomic System Taking into Account its Objective Function - Amelkin, Serghey A. (Interdisciplinary Description of Complex Systems, 2012)
An economic system is considered. The system consists of an active subsystem (a firm). There exists exchange between the firm and two economic reservoirs (markets) which are in environment of the system. Two cases are investigated; they are stationary and nonstationary regimes of the system functioning. The parameters of the market are constant in the stationary regime. Parameters of the market in the nonstationary regime are random; their distributions are known. Expressions for maximal profit and maximal profitability at given profit are obtained. Additional problem is considered for nonstationary regime. It is minimization of risks problem. Optimality conditions for this problem are obtained.